Design and Technology Education and the Concept of Property - Molwane, Olefile Bethuel; Mwendapole, Chinandu (Design and Technology Education: An International Journal, 2008)
Knobler (1971) notes that within society at least three communities are affected by intellectual property rights and these include; the stakeholders who produce and distribute the new knowledge such as Microsoft or Disney, individual generators of new knowledge such as designers and inventors, and the public that seeks access to the created knowledge. This paper considers the inter-relationships between design knowledge and the concept of property. It also addresses the challenges and the implications of this inter-relationships. The paper is divided into six parts. 1. The Introduction 2. Defining the Concept of Property 3. Design and Technology Education in Botswana 4. The Inter-relation between Design Knowledge and The Concept of Property 5. Challenges and Implications for Design and Technology Education 6. Conclusion The paper is informed by documentary findings and case study to illustrate the debate.